Alternative Models of Industrial Relations Graduate Programs in Canadian and U.S. Universities - Chaykowski, Richard; Weber, Caroline (Relations industrielles / Industrial Relations, 1993)
The authors present the debate over whether or not industrial relations constitutes a discipline, and then discuss some of the implications of this debate for the development of industrial relations teaching units and curriculum content. Alternative organizational approaches to graduate-level study of industrial relations in Canada and the United States are broadly characterized as « sovereign Discipline » and « dependent field » models. The authors posit that the teaching model used is a direct reflection of whether or not the field of industrial relations is recognized as a sufficiently independent field of inquiry. Finally, the authors consider some of the factors influencing changes in program content and offer some implications of these factors for the future study of industrial relation.